Pre-analytical sample handling training for histopathology and cytology examination in Jambi province - Fairuz; Dewi, Hasna; Nurhusna; Martawinarti, Rts Netisa; Ekaputri, Kintan Resqitha (Proceedings Academic Universitas Jambi, 2025)
This community service program addressed critical gaps in pre-analytical sample handling procedures for histopathology and cytology examinations across Jambi Province healthcare facilities. Laboratory examination quality depends on proper specimen handling, yet many healthcare workers lack standardized training in tissue and fluid sample collection, fixation, and transportation protocols. The initiative targeted medical personnel from various healthcare institutions, including hospitals, clinics, and laboratory facilities affiliated with the Ministry of Health, National Research and Innovation Agency (BRIN), and Ministry of Education, Culture, Research, and Technology. The program delivered comprehensive training through multiple formats: seminars, hands-on practicum sessions, monitoring activities, and evaluation procedures. Educational content covered specimen collection techniques, fixation methods using formalin, proper labeling systems, and histosave bag technology for anatomical pathology sample transport to ensure specimen integrity. Pre-test and post-test assessments measured knowledge improvement, with results showing increased competency scores across all participant categories (health institutions scoring <50, 50-60, and >60). The training successfully enhanced participants’ understanding of pre-analytical procedures, emphasizing the relationship between proper sample handling and diagnostic accuracy. Participants received guidebooks and histosave materials, establishing standardized protocols for specimen management. This initiative strengthened laboratory quality assurance systems and improved diagnostic capabilities across healthcare facilities, ultimately supporting better patient care through reliable pathological examination results.